2012
DOI: 10.1038/nmat3464
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the superconducting transition temperature of FeSe by intercalation of a molecular spacer layer

Abstract: The tetragonal phase of Fe 1+ Se (0.01 ≤  ≤ 0.04) with the anti-PbO-type crystal structure displays superconductivity (T c ~ 8.5 K) when  = 0.01 and the superconductivity is destroyed by additional interstitial Fe. 9 The compound bears close structural resemblance to LiFeAs 10 (both compounds contain FeQ 4 (Q = Se, As) tetrahedra that are highly compressed in the basal plane compared with other iron-based superconductors) and both compounds differ from the canonical iron-based superconducting system in that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

45
454
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(506 citation statements)
references
References 32 publications
45
454
1
6
Order By: Relevance
“…Through the intercalation of potassium 7) and sodium 8) into FeSe, in fact, the interlayer spacing between neighboring Fe layers, d, has increased from 5.52 Å to 7.02 Å and 6.83 Å, so that T c has increased up to ~ 31 K and ~ 37 K, respectively, while T c of lithium-intercalated FeSe without increase in d has remained 8 K. 9) Further increase in d has been attained through the co-intercalation of alkali or alkaline-earth metals and ammonia, so that d and T c have increased to 7 -11 Å and 31 -46 K in A x (NH 3 ) y Fe 2-z Se 2 (A: alkali or alkaline-earth metals), respectively. 8,[10][11][12][13][14] Following ammonia, several kinds of organic molecules have also been reported to be intercalated into FeSe together with alkali or alkaline-earth metals. In pyridine-intercalated Li 16,17) Collecting these results of the FeSe-based intercalation superconductors, it has been found that T c tends to increase with increasing d and to be saturated at ~ 45 K for d ≥ 9 Å and that the carrier doping of intercalants into the conducting FeSe layer seems not to affect T c so much.…”
Section: Introductionmentioning
confidence: 99%
“…Through the intercalation of potassium 7) and sodium 8) into FeSe, in fact, the interlayer spacing between neighboring Fe layers, d, has increased from 5.52 Å to 7.02 Å and 6.83 Å, so that T c has increased up to ~ 31 K and ~ 37 K, respectively, while T c of lithium-intercalated FeSe without increase in d has remained 8 K. 9) Further increase in d has been attained through the co-intercalation of alkali or alkaline-earth metals and ammonia, so that d and T c have increased to 7 -11 Å and 31 -46 K in A x (NH 3 ) y Fe 2-z Se 2 (A: alkali or alkaline-earth metals), respectively. 8,[10][11][12][13][14] Following ammonia, several kinds of organic molecules have also been reported to be intercalated into FeSe together with alkali or alkaline-earth metals. In pyridine-intercalated Li 16,17) Collecting these results of the FeSe-based intercalation superconductors, it has been found that T c tends to increase with increasing d and to be saturated at ~ 45 K for d ≥ 9 Å and that the carrier doping of intercalants into the conducting FeSe layer seems not to affect T c so much.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-doped FeSe materials can be synthesized using the high-temperature-annealing method [1,[5][6][7][8] and liquidammonia technique [2,3,[9][10][11][12][13][14], and its T c can be increased by increasing the FeSe plane spacing [2,4]. On the other hand, it was found that pressure application resulted in a high-T c phase with the T c reaching a value greater than 45 K [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study on (NH 3 ) y Na x FeSe exhibiting different T c 's, 32 and 46 K [3,12,17], suggested that a difference in the location of metal atoms in each phase resulted in a different FeSe plane spacing, leading to a different T c . This was suggested from the analogy of the FeSe plane spacing and T c of the high-T c (T c = 46 K [3,14]) phase in (NH 3 ) y Na x FeSe with those of (NH 3 ) y Li x FeSe (T c = 44 K [3,10]), while the FeSe plane spacing and T c of the low-T c phase (T c = 32K [12,17]) with those of K x FeSe (T c = 31 K [5]). The Rietveld refinement of the neutron diffraction of (NH 3 ) y Li x FeSe clarified that the Li occupied the 4c and 2b sites and the N of NH 3 occupied the 2a site [10].…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to investigate this latter effect, organic molecular complexes including alkalis were recently intercalated between the FeSe layers [12][13][14][15][16][17][18][19] 15 . The crystal structure of a stoichiometric version of these materials is shown in Fig.…”
mentioning
confidence: 99%